0
$\begingroup$

I have a question which Kind of makes me crazy right now. If I have the equation $1=\ln(2•3)$, I could then use the e function to remove the $\ln.$ Doing that I get $e^1 = 6.$ Now say we are using the rules of the log at the beginning we could write $$1 = \ln(2)+\ln(3).$$ Using the $e$ function I get $e^1 = 2+3$. How is this possible? What is my mistake?

$\endgroup$
4
$\begingroup$

Your mistake is that $e^{\ln 2+\ln 3} = e^{\ln2} \cdot e^{\ln3}$ and not $e^{\ln 2+\ln 3} = e^{\ln2} + e^{\ln3}$.

$\endgroup$
1
$\begingroup$

You can't have the equation like $1 = \log(2\cdot 3)$. It's like saying if you have $2= 3$ and if I add $1$ on both sides then to get $3=4$. Now can I ask how $3=4$?

Moreover if $1 = \log{2} + \log{3}$, then $e^{1} = e^{\log{2}+\log{3}} = e^{\log{2}} \cdot e^{\log{3}} = 2 \cdot 3=6$

$\endgroup$
  • 3
    $\begingroup$ That's not the major mistake. $\endgroup$ – Hendrik Vogt Jul 3 '11 at 13:02
  • $\begingroup$ @Hendrik: Thanks. Yes, I think, I have done it correctly now. $\endgroup$ – user9413 Jul 3 '11 at 13:04

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.